2021
DOI: 10.1097/jcn.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Motivational Interviewing on Self-care and Health-Related Quality of Life in Patients With Chronic Heart Failure

Abstract: BackgroundSelf-care is an integral component of successful chronic heart failure (HF) management. Structured educational programs have already been shown to be effective in improving self-care, but some patients show resistance and little motivation for change.ObjectiveThe objective of this study was to compare efficacy in improving self-care and health-related quality of life (HRQoL) for an educational intervention based on motivational interviewing (MI) compared with a conventional educational intervention.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…It is possible that with adaptations for age, MI may increase its effectiveness among OA. Literature on general psychotherapy with OA (Cook et al, 2005), and specifically on MI, recommends that MI be delivered at a slower pace, with longer and more intensive sessions, and across a longer period of time (e.g., Garcimartín et al, 2022). Such enhancements may have increased MI's effect for OA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that with adaptations for age, MI may increase its effectiveness among OA. Literature on general psychotherapy with OA (Cook et al, 2005), and specifically on MI, recommends that MI be delivered at a slower pace, with longer and more intensive sessions, and across a longer period of time (e.g., Garcimartín et al, 2022). Such enhancements may have increased MI's effect for OA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored non-clinical factors that may be associated with self-care in chronic HF. 12,14,30,31 Heo et al studied 122 patients and found that self-care confidence, the perceived control attitudes and the heart failure knowledge measured with specific scales were related to self-care behaviours. 14 Subsequent studies have showed specifically the association of social support with self-care in patients with heart failure 14,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Addressing behavioural changes of patients in the setting of chronic complex conditions such as heart failure is not an easy task. 12 Self-care is a complex concept and is influenced by modifiable and non-modifiable determinants. Identify modifiable factors as life habits, weight control, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations